Integrating Civic Engagement Into a Lifestyle Intervention for Rural Women – A Mixed Methods Process Evaluation - Sriram, Urshila; Graham, Meredith L; Folta, Sara; Paul, Lynn; Seguin-Fowler, Rebecca A (American journal of health promotion, 2023)
Purpose The present study aimed to evaluate the implementation of a civic engagement curriculum (HEART Club) designed to catalyze positive environmental change in rural communities. Design The HEART Club curriculum was integrated into a six-month community-based health behavior intervention to reduce cardiovascular disease risk. Setting Participants were recruited from eight rural towns in Montana and New York. Subjects 101 midlife and older women. Intervention Participants worked to address an issue related to their local food or physical activity environment and establish progress monitoring benchmarks. Method Evaluation components included after-class surveys, program leader interviews (n = 15), participant focus groups (n = 8), and post-intervention surveys. Results Intervention sites reported high fidelity (78%) to the curriculum. Average attendance was 69% and program classes were rated as highly effective (4.1 out of 5). Despite positive participant feedback, low readiness for civic engagement and insufficient time were implementation challenges. The majority of HEART Club groups had accomplished two or more benchmarks post-intervention. Facilitators of progress included community support, effective leadership, and collective effort. Participants also indicated that trying to affect community change while simultaneously making personal health improvements likely stalled initial progress. Conclusion These findings highlight the potential and challenges associated with civic engagement within the context of rural lifestyle interventions. Future implementation efforts should focus on reframing civic engagement as an approach to support and maintain behavior change.